IMAGOLOGIC ASPECTS OF THE INTERPLAY BETWEEN CHARACTERS IN DARIIA YAROSLAVSKASTOLIARCHUK’S NOVEL «BETWEEN EXTREMES» - Kasiyan, Z. L. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the imagologic diversity of the interplay between the characters in Dariia Yaroslavska-Stoliarchuk’s novel “Between Extremes”. There has been analyzed the issue of acceptance or rejection of “the Other”, preservation of “the Own” and seizing “the Strange”. Attention is focused on the analysis of the ethnic image of the Ukrainian emigrant, who has left native country due to politic beliefs.